Real Marriages, Fake Marriages, and Marriages for Fun: Rituals, Rules, and Transgressions in Early Modern Italy (Sixteenth-Eighteenth Centuries) - Alfieri, Fernanda (Church history and religious culture, 2024)
This essay addresses the topic of “true marriage” by referring especially to a historiographical tradition that in Italy has examined the impact of the norms of the Council of Trent on the sacrament, measuring the effectiveness of their application in the early modern age. After a survey of the studies that, over the course of the 20th century, have observed the nuptial institution from the perspective of social, legal, and cultural history, a series of cases preserved in the Archives of the Dicastery for the Doctrine of the Faith are analyzed. These include a register dedicated to “matrimonia ficta” (fake marriages) involving a diverse set of situations, documented between the late sixteenth and the late eighteenth centuries, in which a wedding-like ritual was enacted, sometimes with both parties being aware of the fictitious nature of the ceremony but more often with one being kept in the dark, to achieve a union that appeared to be a marriage, at once bypassing and moving within the rules. Two cases from the fonds of the Inquisition of Siena complete the body of documents analyzed, paying particular attention to the meaning assigned “from below” to gestures (such as ring exchange or kissing) and to gender relations in the ritual performance.